Konseling Individu Dengan Teknik Cognitif Restructuring Dalam Kekerasan Verbal Orangtua Terhadap Anak - Aini, Aini; Razzaq, Abdur; Jannati, Zhila (CV. ITTC INDONESIA, 2023)
Verbal violence is verbal action that has the effect of violence, either with words that are explicit in the surface structure or words that are implied in a deep structure that are carried out against other people by using words that can hurt other people. The purpose of this study was to find out the description of parental verbal abuse in children, to find out the application of individual counseling with cognitive restructuring techniques, to find out the factors that influence the occurrence of verbal violence in children, to know the description of parental verbal abuse in children after individual counseling with cognitive techniques was applied. restructuring. This type of research is a type of field (field research). Data analysis uses a qualitative method with a case study approach. Data collection tools are observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions/verification. The subject of this research is client